ANALISIS PENGARUH STRES KERJA DAN MOTIVASI EKSISTENSI TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Pegawai Dinas Pertanian Perikanan dan Pangan Kabupaten Semarang) - Ayu Puspita, Isna; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2018)
Job stress and existence motivation experienced by the employees in the organization can affect the employees’ job satisfaction. The employees’ job satisfaction can directly affect the fluctuation of employees’ performance. The aim of this research is to examine and analyze the influence of job stress on job satisfaction, the influence of existence motivation on job satisfaction, the influence of job satisfaction on employees’ performance, the influence of job stress on employees’ performance through job satisfaction as intervening variable and the influence of existence motivation on employees’ performance through job satisfaction as intervening variable. The research population was the employees of Dinas Pertanian Perikanan dan Pangan Kabupaten Semarang that number 187 employees, then 90 employees were chosen as the sample of the research by using quota sampling technique. The method of data analysis used was multiple linear regression analysis. The data testing technique used was path analysis. The path analysis included: test validity, reliability test, classical assumption test, T test, F test, coefficient determination test and sobel test to examine the mediation effect.Based on the result of this research, the researcher concludes that the job stress doesn’t negatively and significantly affect the job satisfaction while the existence motivation positively and significantly affects the job satisfaction. The job satisfaction positively and significantly affects the employees’ performance. The job stress doesn’t negatively and significantly affect the employees’ performance if it is mediated by the job satisfaction, whereas the existence motivation positively and significantly affects the employees’ performance mediated by the job satisfaction.